PENGARUH MEKANISME CORPORATE GOVERNANCE TERHADAP NILAI PERUSAHAAN - Maharani, Windhy Intan (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2013)
This research is meant to find out the influence of corporate governance mechanism to the value of the company. The corporate governance mechanism which measured with 4 variables (the Independent Board of Commissioners, institutional ownership, managerial ownership and audit committee), and the value of the company in this research is measured with the value of Tobinâs Q. This research is using purposive sampling method which listed in Indonesia Stock Exchange (BEI) in during the period of 2007-2011 and it obtains 31 companies as the samples. The analysis method in this research is using multiple linier regressions. The result of this research indicates that the corporate governance mechanism which has proxy with the institutional ownership, the managerial ownership and audit committee which has insignificant negative influence to the value of the company. While, the Independent Board of Commissioners has a significant positive influence to the value of the company. Keywords: The Corporate governance, The Value of The Firm, Tobinâs Q.